2017
DOI: 10.1080/13696998.2017.1284079
|View full text |Cite
|
Sign up to set email alerts
|

Cost-consequence analysis of different active flowable hemostatic matrices in cardiac surgical procedures

Abstract: Outcome differences associated with FLOSEAL vs SURGIFLO that were previously reported in a comparative effectiveness study may result in substantial cost savings for US hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The authors are currently performing simulation modelbased analyses to evaluate the overall differences in cost associated with the FO versus F + G/T hemostasis strategy. Evidence of approximately 1000 iterations from our different 'economic Floseal databases' utilized in a previous cost-consequence analysis of a large retrospective analysis of Floseal and Surgiflo kit with thrombin in major spine surgery cases (Price et al [15]; Makhija et al [23]) found that the use of F was associated with less transfusion use, less operative time and less product volume utilization with these factors resulting in a cost savings of $151 per major and $574 per severe spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The authors are currently performing simulation modelbased analyses to evaluate the overall differences in cost associated with the FO versus F + G/T hemostasis strategy. Evidence of approximately 1000 iterations from our different 'economic Floseal databases' utilized in a previous cost-consequence analysis of a large retrospective analysis of Floseal and Surgiflo kit with thrombin in major spine surgery cases (Price et al [15]; Makhija et al [23]) found that the use of F was associated with less transfusion use, less operative time and less product volume utilization with these factors resulting in a cost savings of $151 per major and $574 per severe spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In another study comparing the use of F to a different flowable hemostatic matrix (Surgiflo) in cardiac surgery, the author concluded that utilization of F vs. Surgiflo in cardiac surgery procedures could potentially avoid 11 major complications, 31 minor complications, 9 surgical revisions, 79 blood product transfusions and 260.3 hours of cumulative operating time, which corresponds to a net annualized saving of $1.5 million ($6256 per surgery) for an average hospital that perform 245 cardiac surgeries per year 14 .…”
Section: Discussionmentioning
confidence: 99%
“…JME peer reviewers on this manuscript have received an honorarium from JME for their review work, but have no relevant financial or other relationships to disclose. 12 Floseal vs. Surgiflo þ thrombin Spine surgery $151 per major surgery, $547 per severe surgery Tackett et al, 2014 13 Floseal vs. Surgicel/Gelfoam Cardiac surgery $8960 per case Makhija et al, 2017 14 Floseal vs. Surgiflo Cardiac surgery $6256 per surgery…”
Section: Declaration Of Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Similarly, US studies of cardiac surgery and spine surgery have shown that, compared with StGM, SmGM can reduce rates of blood product transfusions as well as operating time, again resulting in cost savings. 18,19 These two hemostatic agents have previously been compared in humans. One study of patients undergoing partial nephrectomy showed no significant differences between SmGM and StGM in ischemia time or blood loss.…”
Section: Discussionmentioning
confidence: 99%